The Termination of an Employment Contract Initiated by the Employer’s Will - Bagdanskis, Tomas (Teisė, 2021)
This article systematically analyses new Labour code rules (regulation from July 2017) and the judicial practice of Lithuania relating to the termination of an employment contract initiated by the employer by employer’s will (Labour Code of the Republic of Lithuania, Article 59). It is important to separate this new background of termination from an ordinary one – the termination of an employment contract by the absence of an employee’s fault (Article 57 of Labour code) – and reveal the theoretical and practical aspects and the conclusions in disclosing the true norm meaning. Employers will be able to terminate an employment agreement without the employees’ fault due to the following reasons (Article 57 of Labour code): employee’s work function is no longer required; employee fails to reach the agreed results of work; employee does not agree to change the terms of their employment agreement, place of work, or working regime; employee does not agree to continue employment after business transfer or a part thereof; employer ceases its activities. New rules, indicated in Article 59 of the Labour code (Termination based on employer’s will), says that if an employer intends to terminate an employment agreement due to other reasons, not listed in Article 57 of Labour code, the employee may be served with a 3 business days’ prior written notice and paid a severance pay of at least 6 average monthly salaries.
Keywords: Employment contract; expiration of employment contract; the backgrounds of expiration of employment contract; notice about termination of employment contract; termination of employment contract initiated by the employer by employer’s will and with the absence of an employee’s guilt